Implementation of The Reading Corner Program to Improve Student Literacy at SDK Kekajodho - Woga, Maria Trisanti; Dhiu, Konstantinus Dua; Fono, Yasinta Maria; Ita, Efrida (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
The reading corner is the utilization of a corner of space as a place for students to read and books are provided for reading. The reading corner plays an important role in improving students‘ literacy by providing a comfortable and attractive reading space and providing various reading materials. The purpose of this program is to improve students’ literacy at SDK Kekajodho. The research method used is descriptive qualitative research with a literature writing method and data collection using observation, interview, and documentation techniques. The results of this study show that the implementation of the reading corner can improve student literacy, increase student interest in reading, increase student insight and knowledge, and help teachers create varied learning.